Using Aid to Prevent Conflict: Horizontal inequalities and aid policy. - Brown, G; Stewart, F (Centre for Research on Inequality, Human Security and Ethnicity (CRISE), 2007)
Aid can be a powerful instrument for helping to prevent conflict. One key way it can do this is by contributing to a fair distribution of resources across different groups in society. But today, this issue is largely ignored in aid policy. This briefing explains why inequalities between groups, or ‘horizontal inequalities’, need to be addressed in aid policy, and sets out how this can be done.